The Effect of Periodic Survey Model on Mathematics Achievement among First Grade Students and Their Creative Thinking (Journal of the College of Basic Education, 2022)
The aim of the current research is to find out the effect of the periodic survey form on the achievement of mathematics among middle school students. To verify the research goal, the following zero hypotheses were developed:1) There is no statistically significant difference at the level (0.05) between the average scores of female students in the experimental group who studied according to the periodic survey model and the average of the female students ’scores in the control group who studied in the usual way in the achievement test.2) There is no statistically significant difference at the level (0.05) between the average scores of female students in the experimental group who studied according to the periodic survey model and the average female students ’scores in the control group who studied in the usual way in the creative thinking test. The researchers followed the experimental approach, and used a partial control design for two equivalents with the post test, and the two groups were rewarded for the variables ((IQ test, time age which is calculated by months, previous achievement in mathematics)).The research sample consists of (80) female students from the first intermediate class students, divided into two groups (40) students, an experimental group, and (40) female students, a control group. The researchers prepared the achievement test, the creative thinking test, and the psychometric properties of the two tests were verified. The results showed that there is an effect of teaching according to the periodic survey model and in favor of the experimental group in the academic achievement and creative thinking tests. In light of the results, the two researchers reached the conclusions, and set a set of recommendations and suggestions.